2015
DOI: 10.1093/nar/gkv874
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between SMYD3 and PC4 drives a distinct transcriptional program in cancer cells

Abstract: SET and MYND domain containing protein 3 (SMYD3) is a histone methyltransferase, which has been implicated in cell growth and cancer pathogenesis. Increasing evidence suggests that SMYD3 can influence distinct oncogenic processes by acting as a gene-specific transcriptional regulator. However, the mechanistic aspects of SMYD3 transactivation and whether SMYD3 acts in concert with other transcription modulators remain unclear. Here, we show that SMYD3 interacts with the human positive coactivator 4 (PC4) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 43 publications
2
42
0
1
Order By: Relevance
“…dCas9 fusion proteins have been successfully used in ESC and cancer cell lines to target a number of histone modifiers to specific genomic loci, including a histone demethylase (LSD1/KDM1A) (Kearns et al, 2015), a transcriptional coactivator and histone acetyltransferase (p300) (Hilton et al, 2015; Klann et al, 2017) and histone methyltransferases (SMYD3, PRDM9 and DOT1L) (Kim et al, 2015; Cano-Rodriguez et al, 2016; Kwon et al, 2017) (Fig. 1B).…”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
See 3 more Smart Citations
“…dCas9 fusion proteins have been successfully used in ESC and cancer cell lines to target a number of histone modifiers to specific genomic loci, including a histone demethylase (LSD1/KDM1A) (Kearns et al, 2015), a transcriptional coactivator and histone acetyltransferase (p300) (Hilton et al, 2015; Klann et al, 2017) and histone methyltransferases (SMYD3, PRDM9 and DOT1L) (Kim et al, 2015; Cano-Rodriguez et al, 2016; Kwon et al, 2017) (Fig. 1B).…”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
“…When pursuing modification of specific chromatin marks, the use of the catalytic domain of the epigenetic effector protein, rather than the full-length protein itself, has been shown to be more efficient (Hilton et al, 2015; Kim et al, 2015; Choudhury et al, 2016; Liu et al, 2016; McDonald et al, 2016; Morita et al, 2016; Vojta et al, 2016; Xu et al, 2016; Stepper et al, 2017). Additionally, the majority of epigenetic engineering tools use amino acid linkers between the dCas9 protein and the effector domain to create a fusion protein.…”
Section: Technical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…26, 27 Studies have reported that SUB1 interacts with distinct domains of activators such as VP16, GAL4, AP2, HIV-TAT, P53 and SMYD3 to modulate their functions. 19, 22, 2832 Previous studies indicated that the overexpression of SUB1 in a population of normal dermal multipotent fibroblasts resulted in the tumorigenic transformation of the cells, indicating its role in tumorigenesis. SUB1 has been recently found to show an upregulated level in different cancers.…”
Section: Introductionmentioning
confidence: 99%